Maximum entropy power laws: An application to the tail of wealth distribution - Mishael Milaković (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2002)
Statistical equilibrium denotes the distribution of wealth that can be achieved in the largest number of ways while satisfying a first moment constraint on the rate of growth in wealth portfolios. Maximizing entropy subject to a logarithmic constraint yields a power law distribution whose characteristic exponent depends positively on the minimum wealth level, and inversely on the rate of growth and the average number of changes in the composition of wealth portfolios. Put differently, the distribution of wealth will be more unequal the faster the rate of growth in wealth and also the higher the number of turnovers.
Keywords: 330; wealth distribution; power laws; statistical equilibrium; maximum entropy; Vermögensverteilung; Entropie; Lorenz-Kurve